Design and Build a Web App-Based Conference Registration System Using the Waterfall Model - Fawaidul Badri; Ridwan Maulana; Khusnul Khotimah; Rizqi Putri Nourma Budiarti; Awang Andhyka (TEKNOLOGI DITERAPKAN DAN JURNAL SAINS KOMPUTER, 2021)
During the pandemic, many events are held online. conference registration (webinars, seminars, workshops) which basically will cause its complexity for admins if there are excess registrants or over participants from achieving the registration quota target. In addition, the admin must monitor regularly to ensure that there are no excess registrants that result in inefficient. The method used in the development of this application is the waterfall method. The purpose of this research is to build a web-based conference registration system that can make it easier for admins/organizers to manage the registration process. The results of this study the system can display the results of the recap from the admin so that the user can see the quota from the conference registration organized by the committee as well as testing of users from several tests to produce an application system that runs well.